The tRNA methyltransferase Dnmt2 is required for accurate polypeptide synthesis during haematopoiesis. (19th August 2015) - Tuorto, Francesca; Herbst, Friederike; Alerasool, Nader; Bender, Sebastian; Popp, Oliver; Federico, Giuseppina; Reitter, Sonja; Liebers, Reinhard; Stoecklin, Georg; Gröne, Hermann‐Josef; Dittmar, Gunnar; Glimm, Hanno; et al.
Abstract The Dnmt2 enzyme utilizes the catalytic mechanism of eukaryotic DNA methyltransferases to methylate several tRNAs at cytosine 38. Dnmt2 mutant mice, flies, and plants were reported to be viable and fertile, and the biological function of Dnmt2 has remained elusive. Here, we show that endochondral ossification is delayed in newborn Dnmt2‐deficient mice, which is accompanied by a reduction of the haematopoietic stem and progenitor cell population and a cell‐autonomous defect in their differentiation. RNA bisulfite sequencing revealed that Dnmt2 methylates C38 of tRNA AspGTC, GlyGCC, and ValAAC, thus preventing tRNA fragmentation. Proteomic analyses from primary bone marrow cells uncovered systematic differences in protein expression that are due to specific codon mistranslation by tRNAs lacking Dnmt2‐dependent methylation. Our observations demonstrate that Dnmt2 plays an important role in haematopoiesis and define a novel function of C38 tRNA methylation in the discrimination of near‐cognate codons, thereby ensuring accurate polypeptide synthesis.